Hippocampal Neuroimaging‐Informed Clinical Trial Enrichment Tool for Amnestic Mild Cognitive Impairment Using Open Data. Issue 4 (7th March 2020) - Conrado, Daniela J.; Burton, Jackson; Hill, Derek; Willis, Brian; Sinha, Vikram; Stone, Julie; Coello, Neva; Wang, Wenping; Chen, Danny; Nicholas, Timothy; Gold, Michael; Hartley, Emily; et al.
Abstract : Our goal was to assess the enrichment utility of hippocampal volume (HV) as an enrichment biomarker in amnestic mild cognitive impairment (aMCI) clinical trials, and, hence, develop an HV neuroimaging‐informed clinical trial enrichment tool. Modeling of integrated longitudinal patient‐level data came from open‐access natural history studies in patients diagnosed with aMCI—the Alzheimer's Disease Neuroimaging Initiative (ADNI)‐1 and ADNI‐2—and indicated that a decrease of 1 cm 3 with respect to the analysis dataset median baseline intracranial volume‐adjusted HV (ICV‐HV; 5 cm 3 ) is associated with > 50% increase in disease progression rate as measured by the Clinical Dementia Rating Scale–Sum of Boxes. Clinical trial simulations showed that the inclusion of aMCI subjects with baseline ICV‐HV below the 84th or 50th percentile allowed an approximate reduction in trial size of at least 26% and 55%, respectively. This clinical trial enrichment tool can help design more efficient and informative clinical trials.